Latrine Ownership and Soil-Transmitted Helminth Infection in a Rural Indonesian Setting: A Cross-Sectional Study from Mataredi, Central Sumba - Sabawali, Jeremias Awang Bagas; Deo, Dwita Anastasia; Koamesah, Sangguana Marthen Jacobus; Buntoro, Ika Febianti (Jurnal Biologi Tropis, 2025)
Soil-transmitted helminth (STH) infection remains a public health concern in rural tropical settings, where limited sanitation and high environmental exposure elevate risk. In Mataredi Village, most residents are subsistence farmers with constrained access to improved sanitation. Objective to estimate the prevalence of STH infection and assess its association with household latrine ownership in Mataredi Village, Katikutana District, Central Sumba. Methods: An analytical cross-sectional study was conducted in June–July 2024. A total of 144 residents aged >5 years who met inclusion criteria were enrolled using consecutive sampling. Fresh stool samples were examined by direct smear with 2% Lugol’s iodine. The association between latrine ownership (yes/no) and STH infection status (positive/negative) was evaluated using the Chi-square test; results are presented as p-value and odds ratio (OR) with 95% confidence interval (CI). Overall prevalence of STH infection was 19.4% (28/144). The species profile was dominated by Trichuris trichiura, with both single and mixed infections detected. Based on the Chi-square test, there was no statistically significant association between latrine ownership and STH infection (p = 0.943; OR 0.88; 95% CI 0.38–2.06). A mass deworming campaign conducted in May 2024 may have reduced detectable worm burden and attenuated observed associations.  The prevalence of STH infection in Mataredi Village was 19.4%, with Trichuris trichiura predominance. No significant association was found between household latrine ownership and infection status.